“Take Me Back to My Homeland Dead or Alive!”: The Myth of Return Among London’s Turkish-Speaking Community - Cakmak, Mustafa (Frontiers in Sociology, 2021)
In classical diaspora literature, the ‘myth of return’ has major significance. It is believed that the ‘myth of return’ is embedded in the minds of immigrants from their arrival. This paper examines post-migration mobilities of the Turkish-speaking community in North London as well as the shift in narratives of homeland among diaspora communities; from the ‘myth of return’ to ritual-like visits or mundane pilgrimages. My ethnographic study analyses the post-migration homeland visiting patterns of the Turkish-speaking community into four categories. I discuss how narratives of episodic homeland visits and the desire to be buried in the homeland have replaced the myth of return.